Deteksi Dini Perubahan Nilai GDS pada Olahragawan dalam Upaya Pencegahan Penggunaan Doping - Siti Rahmani; Sri Wahyuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to see changes in GDS values in athletes to prevent doping use. This study uses quasi-experimental research with a one-group pre-test-post-test design. The results showed that the shift in GDS values in futsal players decreased by an average of 5 mg/dl, in swimmers, the standard decreased by 8 mg/dl, 100 M runners decreased by an average of 4 mg/dl, and the average value decreased in GDS values. On mobile legend e-sport players, only 1 mg/dl. In conclusion, the types of sports that experienced the most decrease in GDS occurred swimming, then futsal, 100 M running, and e-sports players. Blood glucose values will decrease more and more if a person does activities with more use of body movement. Cold temperatures will increase the body's ability to produce energy which will maintain body temperature within normal limits. Keywords: Doping, Blood Glucose During (GDS), Athlete